HIV prevention clinical trials' community engagement guidelines: inequality, and ethical conflicts. Issue 1 (1st January 2020) - Folayan, Morenike O.; Peterson, Kristin
ABSTRACT: In 2004 and 2005, the first clinical trials were launched to investigate the use of tenofovir for HIV prevention in Cambodia, Cameroon, Nigeria and Thailand. Controversies erupted over the ethical integrity of the research protocol. We reflect on the events that led to the controversies and identified that scientific and ethical concerns raised by members of local communities at each of these sites were erased by trialists, causing crisis that led to premature shut down the early PrEP trials. In the aftermath of these trials, the World Health Organisation, UNAIDS, and AVAC developed ethics guidelines intended to recognize the concerns as authentic, and developed guidelines to improve researchers' engagement of communities in biomedical HIV prevention trial design and implementation. Our findings suggest that the ethics guidelines are limited in its ability to address power inequalities that leads to voice erasures and non-recognition of local competencies. Rather the ethical documents enabled trialists to gain a new sense of authority through the interpretations of ethical research conduct enabling trialists regain power that can further entrench inequality and voice erasures. To address concerns with what seems an intractable problem, we suggested models of engagement for off-shored research may be the option.